Which Non-Pharmacological Treatment is More Effective on Clinical Parameters in Patients With Fibromyalgia: Balneotherapy or Aerobic Exercise? - Emine Eda KURT,; Fatmanur Aybala KOÇAK,; Hatice Rana ERDEM,; Figen TUNCAY,; Feyzanur KELEZ, (Archives of Rheumatology, 2016)
Objectives: This study aims to determine the effects of non-pharmacological therapies, namely balneotherapy, exercise, and the combined use of balneotherapy and exercise, on total myalgic score (TMS), sleep quality, health status, and signs of depression in patients with fibromyalgia syndrome, and to compare the efficacies of these treatment programs with respect to the above parameters. Patients and methods: A total of 120 female subjects (mean age 37.21±12.45 years; range 18 to 63 years) diagnosed with fibromyalgia were enrolled. The patients were randomized into three groups with 40 patients in each (group 1: balneotherapy group, group 2: balneotherapy + exercise group, and group 3: exercise group). The patients underwent the treatment program for five days a week for a total of three weeks. Clinical parameters, Fibromyalgia Impact Questionnaire, Pittsburgh Sleep Quality Index, TMS, and Beck Depression Scale were evaluated at pre-treatment and post- treatment periods, and at the third-month control visit. Results: There were no differences between the groups with respect to Fibromyalgia Impact Questionnaire, Pittsburgh Sleep Quality Index, TMS and Beck Depression Scale scores on pre-treatment evaluation, while the combined use of balneotherapy + aerobic exercise was more effective on TMS (p<0.001), health status (p=0.009), and level of depression (p<0.001) in post-treatment evaluation. A better state of well-being with respect to sleep quality was achieved by balneotherapy and balneotherapy + exercise groups. The third-month comparisons, on the other hand, demonstrated that the balneotherapy + exercise group had a greater state of well-being with respect to TMS (p<0.001) and general health status (p<0.001). Balneotherapy + exercise and exercise therapy benefited signs of depression to a better degree (p<0.001). Balneotherapy and combined balneotherapy + exercise therapy produced more effective results in terms of sleep quality (p<0.001). TMS regressed to near baseline levels (p=0.397), while Fibromyalgia Impact Questionnaire levels rose to near baseline levels at the third-month control in the exercise therapy group (p=0.070). Conclusion: The combined application of balneotherapy + exercise therapy, which are two of the recommended non-pharmacological treatments, may have superior and more sustained effects than administering either therapy alone.